SEJARAH MUNCULNYA TASAWUF - Abdul Wahab Syakhrani; Nournaina Nournaina (Cross-border, 2023)
Sufism does not only originate from Islam, but is also influenced by external Islamic teachings, namely: Christian elements, Hindu-Buddhist elements, Greek elements, and also Persian and Arabic elements. Islamic law. The important thing is how we can always try to get closer to Allah SWT by making Islamic law as a guide to reach the truth.